Molecular Technique Identification Of The Microbial Population In Palm Oil Mill Effluent (Pome) - Wei, Christy Chan Sien; Lau, Seng; Awang Ahmad Sallehin, Awang Husaini; Azham, Zulkharnain; Kasing, Apun; Leslie, Bilung; Micky, Vincent (MOPB, 2015)
Bioconversion of palm oil mill effluent (POME) to generate methane gas via anaerobic digestion involves a consortium of microbes which are responsible in several steps of the biodegradation process. In this study, the microbial community from a selected POME was characterised via molecular techniques and through culture-based plating in order to determine their composition, and subsequently understand their function in the anaerobic community. Genomic DNA of the microbial community was extracted using direct extraction technique, followed by PCR targeting the 16S rDNA region. Distinct fragments of approximately 1100 bp in sizes were successfully amplified using PCR and cloned onto Escherichia coli XL-1 Blue. Upon sequencing of the fragments, BLAST queries identified the bacteria as Thermoanaerobacterium sp. In addition, two other bacterial species were successfully isolated from the POME by culturing on DVS agar. The sequencing result of these bacterial isolates showed both isolates belonged to the Bacillus genus. By understanding the bacterial community present in the POME, this will lead to the improvement of the anaerobic digestion process to enhance the production of biogas such as methane.